Investigation on behavior of concrete slab due to low velocity impact using numerical modeling - Syamsir A.; Islamiah S.; Norhisham S.; Kamal N.L.M.; Nor N.M.; Anggraini V. (Springer Science and Business Media Deutschland GmbH, 2023)
Offshore oil well production; Drop height; Linear region; Low velocity impact; Slab thickness; Steel balls; Concrete slabs